To What Extent are International Organizations (IOs) Autonomous Actors in World Politics? - Alexander Andreev (Opticon1826, 2007)
The role of International Organisations is becoming increasingly significant and, sometimes, ultimate for international policy-making, the process coming along with the globalisation of world politics. There are 1,963 IOs in the world today and they deal extensively both with global challenges and countryspecific issues1. The number of IOs is constantly growing, as well as their impact on world matters. The major and most significant IOs are those of the UN system, but there are also key intercontinental and regional organisations. It will be true to say that today the independent behaviour of state actors is becoming more limited because of their obligations to international and regional agreements, regimes and institutions. The reality of growing complex interdependence facilitates a structure of global governance, radically challenging state-centric approaches to international policy-making.
Keywords: policy-making; globalisation; non-state actors